HEVC Complexity and Implementation Analysis - Bossen, F.; Bross, B.; Suhring, K.; Flynn, D. (IEEE transactions on circuits and systems for video technology, 2012)
Advances in video compression technology have been driven by ever-increasing processing power available in software and hardware. The emerging High Efficiency Video Coding (HEVC) standard aims to provide a doubling in coding efficiency with respect to the H.264/AVC high profile, delivering the same video quality at half the bit rate. In this paper, complexity-related aspects that were considered in the standardization process are described. Furthermore, profiling of reference software and optimized software gives an indication of where HEVC may be more complex than its predecessors and where it may be simpler. Overall, the complexity of HEVC decoders does not appear to be significantly different from that of H.264/AVC decoders; this makes HEVC decoding in software very practical on current hardware. HEVC encoders are expected to be several times more complex than H.264/AVC encoders and will be a subject of research in years to come.